The effects of training intervention on the prevention of knee joint injuries: a systematic review and meta-analysis - Zheng, G.; Zeng, S.; Li, T.; Guo, L.; Li, L. (Frontiers in Physiology, 2025)
Objective: To evaluate the impact of neuromuscular, core strength, balance, and proprioceptive training on preventing knee injuries in young athletes, to identify optimal intervention characteristics.